Influence of Crown Ferrule Heights and Dowel Material Selection on the Mechanical Behavior of Root-Filled Teeth: A Finite Element Analysis - Watanabe, Mauricio U.; Anchieta, Rodolfo Bruniera [UNESP]; Rocha, Eduardo Passos [UNESP]; Kina, Sidney [UNESP]; de Almeida, Erika Oliveira [UNESP]; Freitas Junior, Amilcar Chagas [UNESP]; Basting, Roberta Tarkany (Wiley-Blackwell, 2012)
Purpose: This study used the 3D finite element (FE) method to evaluate the mechanical behavior of a maxillary central incisor with three types of dowels with variable heights of the remaining crown structure, namely 0, 1, and 2 mm. Materials and Methods: Based on computed microtomography, nine models of a maxillary central incisor restored with complete ceramic crowns were obtained, with three ferrule heights (0, 1, and 2 mm) and three types of dowels (glass fiber = GFD; nickel-chromium = NiCr; gold alloy = Au), as follows: GFD0 restored with GFD with absence (0 mm) of ferrule; GFD1 similar, with 1 mm ferrule; GFD2 glass fiber with 2 mm ferrule; NiCr0 restored with NiCr alloy dowel with absence (0 mm) of ferrule; NiCr1 similar, with 1 mm ferrule; NiCr2 similar, with 2 mm ferrule; Au0 restored with Au alloy dowel with absence (0 mm) of ferrule; Au1 similar, with 1 mm ferrule; Au2 similar, with 2 mm ferrule. A 180 N distributed load was applied to the lingual aspect of the tooth, at 45 degrees to the tooth long axis. The surface of the periodontal ligament was fixed in the three axes (x = y = z = 0). The maximum principal stress (smax), minimum principal stress (smin), equivalent von Mises (svM) stress, and shear stress (sshear) were calculated for the remaining crown dentin, root dentin, and dowels using the FE software. Results: The smax (MPa) in the crown dentin were: GFD0 = 117; NiCr0 = 30; Au0 = 64; GFD1 = 113; NiCr1 = 102; Au1 = 84; GFD2 = 102; NiCr2 = 260; Au2 = 266. The smax (MPa) in the root dentin were: GFD0 = 159; NiCr0 = 151; Au0 = 158; GFD1 = 92; NiCr1 = 60; Au1 = 67; GFD2 = 97; NiCr2 = 87; Au2 = 109. Conclusion: The maximum stress was found for the NiCr dowel, followed by the Au dowel and GFD; teeth without ferrule are more susceptible to the occurrence of fractures in the apical root third.
Keywords: Crown ferrule; glass fiber dowel; metallic cast; finite element analysis